1984
DOI: 10.1088/0022-3719/17/34/024
|View full text |Cite
|
Sign up to set email alerts
|

Uniaxial stress studies of the Be pair bound exciton absorption spectrum in silicon

Abstract: Abstract.We report the results of preliminary uniaxial stress studies of the beryllium pair isoelectronic bound exciton absorption spectrum in silicon. Our results confirm that the exciton behaves as an isoelectronic acceptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…However, it is consistent with Zeeman experiments, in that the Zeeman splittings were found to be simplest for the [111] direction. It is also consistent with data on the uniaxial stress dependence of the low temperature luminescence [7,14] that shows that the symmetry axis is the [111] axis [8].…”
Section: Pair Defectssupporting
confidence: 90%
See 2 more Smart Citations
“…However, it is consistent with Zeeman experiments, in that the Zeeman splittings were found to be simplest for the [111] direction. It is also consistent with data on the uniaxial stress dependence of the low temperature luminescence [7,14] that shows that the symmetry axis is the [111] axis [8].…”
Section: Pair Defectssupporting
confidence: 90%
“…Furthermore it is believed that the inactive defects are neutral Be pairs [2] that behave as "isoelectronic centers". The isoelectronic Be center in Si has been studied experimentally with infrared absorption [3], photoluminescence [4,5], Zeeman measurements [6], and light absorption while under uniaxial stress [7]. From these studies the microscopic structure of the isoelectronic center was indirectly concluded to be either a substitutional-interstitial Be pair [2] or a Be pair occupying a single substitutional site (an "interstitialcy" or split interstitial) [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One may therefore assume some kind of a neutral Mg-impurity complex or an Mg-related isoelectronic centre which consists of a pair of Mg atoms sharing the substitutional site to be involved in the recombination process. The second assumption is very close to a recombination process involving excitons bound to Be isoelectronic acceptors [9][10][11]. According to their temperature behaviour, lines 16 and 20 could then be attributed to transitions from |J, M J exciton states with total angular momenta J = 2 and J = 1, respectively, to J = 0 ground states.…”
Section: Discussionmentioning
confidence: 83%
“…The appearance of narrow no-phonon lines deep in the energy gap is often explained by recombination of excitons bound to isoelectronic centres [9][10][11]. Indeed, a typical property of most deep impurities is their ability to form complexes with other impurities.…”
Section: Discussionmentioning
confidence: 99%